MULTIDISCIPLINARY APPROACH TO THE PATIENT WITH CEREBRAL PALSY - Poláková, Marcela; Dimunová, Lucia (Profese Online, 2014)
Aim: Disease of cerebral palsy can be described as neurodevelopmental disability non-progressive brain, which causes disruption of motor development children. Often spans multiple areas of development - combined with intellectual disabilities, sensory defects, and affects the development of communications kills. The aim of the study was to develop a new theory using metaparadigm nursing, using a "grounded theory", which would prove the validity and correlation nursing care to every sphere of life (physical, psychological, social, legislative) for those affected children.Methods: Are working-out complex casuist of three case. On inquiries are elect method semistructured conversation and method study health documentation title person. Complex casuist are analyzing method "grounded theory".Results: Information that are acquirement us offer precious expression following those are create new theory with metaparadigm nursing by methods "grounded theory", which mention causality relation nursing care with region life (physically, psychic, social, legislative) child with spastic form infantile cerebral palsy and which also points to the need for multidisciplinary cooperation experts in neurology, physiotherapy, psychology, speechtherapy, special education and social interaction with in the area of the patients.Conclusion: Our theory shows that quality nursing care, comprehensive multidisciplinary approach experts in neurology, physiotherapy, psychology, special education and social care can improve the living conditions of chilren with cerebral palsy in its holistic range.
Keywords: infantile cerebral palsy; multidisciplinary approach; nursing care; complex casuistics; grounded theory